Nicaragua : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility Request for Waivers of Performance Criteria and Financing Assurances Review, Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nicaragua; Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waivers of Performance Criteria, and Financing Assurances Review-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nicaragua. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The draft 2004 budget passed by the assembly is consistent with the Financial Sector Assessment Program (FSAP). Achieving the programmed strengthening of the tax effort remains a challenge. On the expenditure side, the aim is to improve the anti-poverty and pro-growth orientation of public spending. The operating surplus of state enterprises is improved in 2004. The stance of monetary policy is appropriate, as evidenced by the continued achievement of the program objectives for Net International Reserves (NIR) and inflation (in the context of the crawling peg regime).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; International Agreements and Observance; International Organizations; Monetary Policy